Discovery of a self-assembling and self-adjuvant lipopeptide as a saccharide-free peptide vaccine targeting EGFRvIII positive cutaneous melanoma. (12th March 2018) - Chen, Yujuan; Yuan, Fengjiao; Jiang, Xian; Lv, Qing; Luo, Na; Gong, Changyang; Wang, Chunting; Yang, Li; He, Gu
Abstract : Recently, tumor immunotherapy has achieved great progress in the treatment of hematological and solid neoplasms. Abstract : Recently, tumor immunotherapy has achieved great progress in the treatment of hematological and solid neoplasms. The DC vaccines, KLH-conjugated vaccines or glycosylated peptide vaccines can efficiently induce immune responses against tumors. In the current study, we have discovered cholesteryl PADRE-EGFRvIII epitope-conjugated lipopeptide self-assembled micelles as a potential self-adjuvant vaccine against cutaneous melanoma. The lipopeptide vaccines were synthesized using a standard solid phase peptide synthesis method, and these vaccines could elicit both a humoral and a cellular immune response to EGFRvIII positive melanoma cells. Their high humoral immunoreaction stimulation properties in combination with their cytotoxic T-cell eliciting properties provide them with potent tumor inhibitory capacity. In therapeutic and preventive xenograft models of B16-EGFRvIII melanoma cells, the self-adjuvant lipopeptide vaccine micelles efficiently prevented tumor growth as well as tumorigenesis. Our results provide a novel platform for eliciting immune responses to non-antigenic cancer-related epitopes in peptide cancer vaccine discovery and development.